2020
DOI: 10.1002/cre2.339
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, knowledge and treatment decisions for erosive tooth wear: A case‐based questionnaire among Danish dentists

Abstract: Objective To examine the knowledge and experience of erosive tooth wear (ETW) among Danish dental practitioners and, based on two cases, explore their treatment decisions. Methods We sent a validated questionnaire electronically to all active members of The Danish Dental Association and The Association of Public Health Dentists in Denmark. The questionnaire had two parts; the first focused on scoring, recordkeeping, knowledge and experience of ETW. The second part presented two patients with different severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…erefore, a minimal invasive conduct is the best option in most cases [23]. e treatment decisions of teeth affected by dental erosion among Nordic dentists have been evaluated [100][101][102]. Identifying, limiting, or eliminating the acid exposures are important aims for the dentist and the patient.…”
Section: Genes Function Results and Conclusion Referencementioning
confidence: 99%
“…erefore, a minimal invasive conduct is the best option in most cases [23]. e treatment decisions of teeth affected by dental erosion among Nordic dentists have been evaluated [100][101][102]. Identifying, limiting, or eliminating the acid exposures are important aims for the dentist and the patient.…”
Section: Genes Function Results and Conclusion Referencementioning
confidence: 99%
“…Thirteen articles reported information on general/unspecific dietary assessment practices (e.g., dietary analysis, dietary history, assessment of dietary habits, asking about dietary behaviour, diet history review and analysis) of oral health professionals (cross-sectional survey studies (n = 10) [33,36,38,39,41,42,44,[46][47][48]; chart review studies (n = 2) [52,53], qualitative interview study (n = 1) [54]). Most of the articles reported information regarding these practices in dentists.…”
Section: General/unspecific Dietary Assessment Practicesmentioning
confidence: 99%
“…These studies were conducted in pediatric dentists and found that this activity was common in the population of interest (e.g., >90% of pediatric dentists who performed infant oral health evaluations reported this practice [36]; 70.6% of pediatric dentists reported doing a diet history review and analysis regarding dental caries prevention [44]). Several cross-sectional survey studies also reported self-reported information on frequency of providing some type of general/unspecific dietary assessment practice [33,38,39,42,[46][47][48]. Overall, these studies were conducted regarding these practices when assisting patients with specific dental conditions (e.g., root caries [39], erosive tooth wear [38,[46][47][48]) and in children [33,42] and adult [42] patient groups.…”
Section: General/unspecific Dietary Assessment Practicesmentioning
confidence: 99%
See 2 more Smart Citations